The Effects of Using Styrene-Butadiene-Styrene and Fly Ash Together on the Resistance to Moisture-Induced Damage, Permanent Deformation and Fatigue of Hot Mixture Asphalt - Alataş, Taner; Kizirgil, Mustafa Ethem (My University, 2013)
In this study, the effects of combined utilization of Styrene-Butadiene-Styrene (SBS) in bitumen modification and fly ash in modification of mixtures on the mechanical properties of hot mix asphalts were investigated. Within the scope of this study, 12 different mixtures were obtained by combination of three different proportions of SBS additive relative to the total bitumen mass (0, 3 and 6 wt.%) with four different proportions of fly ash replacement relative to the total aggregate mass (0, 2, 4 and 6 wt.%). As a result of these tests, the use of fly ash was found to reduce the Optimum Bitumen Content (OBC), while the use of SBS increased the OBC. It was determined that the individual utilization of SBS and fly ash improved the stability of the mixtures, resilience at normal temperatures, resistance against moisture-induced damage, fatigue life and strength against permanent deformation. In addition, it was found that using only SBS in bitumen modification at 3 wt.% without using fly ash and the use of only fly ash as filler at a proportion of 6 wt.% with pure bitumen yielded similar results. The combined usage of SBS and fly ash was ascertained to boost the associated positive effects, while a comparison of separate additions showed that SBS is more effective than fly ash. Besides, it was also detected that as the SBS content in the mixture increased, the effectiveness of fly ash decreased.
SBS VE UÇUCU KÜLÜN BİRLİKTE KULLANIMININ NEM HASARINA BAĞLI DİRENÇ, KALICI DEFORMASYON VE SICAK BİTÜMLÜ KARIŞIMLARIN YORULMASI ÜZERİNDEKİ ETKİLERİ
Makale - Yabancı Dilde Makale
Keywords: hot mix asphalt; additive; fly ash; sbs; mechanical properties